The nephroprotective potential of diosgenin against ischemia-reperfusion acute renal damage via suppression of oxidative stress and downregulating inflammatory mediators. Issue 1 (1st January 2021) - Mishra, Prachi; Mandlik, Deepa; Arulmozhi, S; Mahadik, Kakasaheb
ABSTRACT: Renal ischemia/reperfusion injury (I/R) is caused by short impairment of the blood supply to the kidney. Acute renal damage (ARD) is still a major problem in today's clinical practice. Diosgenin (DG), a steroidal sapogenin mainly present in fenugreek, yams, Costus  species in high amounts. DG as a leading phytoconstituents is beneficial in several disease conditions due to its multifunction including antioxidant, hypolipidemic, anti-inflammatory, hypoglycemic, anticancer and anti-proliferative effects. The purpose of this study was to investigate the nephroprotective potential of DG on ischemia-reperfusion induced kidney damage in rats. Thirty male Wistar rats were divided into five groups. DG was given orally at doses of 20, 40 and 80 mg/kg for 10 days. On day 11th ARD was induced by unilateral ischemia for 45 min followed by 24-hour reperfusion. The levels of creatinine, blood urea nitrogen, total proteins, pro-inflammatory cytokines were decreased in DG + I/R rats compared to NC rats, along with a significant amelioration of oxidative stress. Histopathological analysis exhibited less histological damage in DG + I/R rats as compared with NC rats. Pretreatment of rats with DG (40 and 80 mg/kg) was able to improve these damages significantly, though DG (20 mg/kg) was insignificantly effective. In conclusion, DG proved nephroprotective potential against kidney damage induced by I/R injury via mitigation of inflammation, oxidative stress, and histopathologic injuries.